(untitled) (Journal of Imam Al-Kadhim College, 2026)
The paper aims to analyze how Western and Middle Eastern media looks to Al-Assad’s collapse. The reporters’ ideologies play an essential role in showing this issue to the reader. The aim is fulfilled by an analysis of certain reports during the coverage of Al-Assad’s collapse. These reports employ definite linguistic choices to manipulate the collapse. The analysis is achieved in the light of transitivity and the lexical selections of Systemic Functional Linguistics. The research concludes that the reporters manipulate linguistic selections in order to influence readers’ perceptions and views, that some reporters support Al-Assad’s regime collapse, considering it as the beginning of freedom for the Syrian people, while others see it as the beginning of freedom as well as the beginning of crises and uncertain future without any regime at the same time. The study also concludes that the material processes are the most adopted choices. Verbs of doing and happening are dominant in the coverage.